Some Biological Applications and Mechanistic Insights of Benzaldehyde‐Substituted Thiosemicarbazones and Their Metal Complexes: A Review - Ekhlakh Veg; Kulsum Hashmi; Mohammad Imran Ahmad; Seema Joshi; Abdul Rahman Khan; Tahmeena Khan (Natural Sciences)
ABSTRACT Thiosemicarbazones (TSCs) and their metal complexes have been subjected to study over several decades. Their medicinal importance as anticancer, antioxidant, antimicrobial, and antidiabetic has been explored. Continual efforts have been made toward activity enhancement that can be achieved by making suitable structural alterations or by studying structure–activity relationship (SAR). This review article focuses on TSCs derived from benzaldehyde moiety and their metal complexes in search of their antimicrobial and anticancer properties. Benzaldehyde and its derivatives are found in many natural systems. This is a first‐of‐its‐kind review, where the emphasis has been laid on one specific moiety and how the substitution in the moiety alters the biological activity. The article also describes the synthesis and reaction conditions of these derivatives. A comprehensive literature survey reveals that benzaldehyde TSCs suppressed the formation of mycolic acid and have also emerged as tyrosinase inhibitors. The effect of the presence of electron‐donating/withdrawing groups has also been disseminated, showing that the substituents bonded to the phenyl ring have a considerable effect on the overall activity, particularly the electron‐donating groups. Likewise, the presence of the hydroxyl group in the para position enhanced the scavenging activity of the compound. The presence of a conjugated tridentate donor set consisting of N, N, and S atoms also affects the anticancer activity of the benzaldehyde‐derived TSC. The mechanistic insights of TSCs, particularly their role in the inhibition of ribonucleoside diphosphate reductase (RR), Topoisomerase II, P‐glycoprotein (P‐gp), generation of reactive oxygen species (ROS), and multidrug resistance (MDR), have also been addressed. The review focuses on benzaldehyde‐derived thiosemicarbazones (TSCs) and their metal complexes. Anticancer and antimicrobial activities of benzaldehyde‐derived TSCs have been elaborated with suitable examples. Mechanistic insights of the anticancer activity and antibacterial activity are also explained. The effect of the presence of electron‐donating /withdrawing groups has also been elaborated.